Purification, crystallization and preliminary X‐ray characterization of the third ScaB cohesin in complex with an ScaA X‐dockerin from Acetivibrio cellulolyticus. Issue 5 (1st May 2014) - Cameron, Kate; Alves, Victor D.; Bule, Pedro; Ferreira, Luís M. A.; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> Interactions between cohesin and dockerin modules are critical for the formation of the cellulosome, which is responsible for the efficient degradation of plant cell‐wall carbohydrates by anaerobes. Type I dockerin modules found in modular enzymatic components interact with type I cohesins in primary scaffoldins, enabling the assembly of the multi‐enzyme complex. In contrast, type II dockerins located in primary scaffoldins bind to type II cohesins in adaptor scaffoldins or anchoring scaffoldins located at the bacterial envelope, contributing to the cell‐surface attachment of the entire complex. Acetivibrio cellulolyticus possesses an extremely complex cellulosome arrangement which is organized by a primary enzyme‐binding scaffoldin (ScaA), two anchoring scaffoldins (ScaC and ScaD) and an unusual adaptor scaffoldin (ScaB). An ScaA X‐dockerin mutated to inactivate one of the two putative cohesin‐binding interfaces complexed with the third ScaB cohesin from A. cellulolyticus has been purified and crystallized and data were collected to a resolution of 2.41 Å.